2020
DOI: 10.1088/2631-8695/ab82eb
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NOCOLOK® flux dry-off temperature on mechanical properties of brazed joint for automotive aluminum-based heat exchangers

Abstract: The drying temperature of the flux at a normal atmosphere has a crucial role in brazing quality in automotive aluminum-based heat exchangers. Throughout this research, NOCOLOK® flux consists of two phases of K2AlF5.H2O and KAlF4 with a melting point around 580 °C was used. A flux slurry was applied on the base metal and dried at 220, 300 and 380 °C in air. The mechanical assessment revealed that when flux dried at 300 °C, the joint withstand maximum shear stress of 44 MPa with complete bonding. At 220 °C and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The use of the wet method increases the risk of contamination of the flux suspension with, for example, dust, metal particles and so on, and requires additional drying after the application process. Milani [33] showed that proper drying influences the mechanical properties of brazed joints and reduces the number of defective heat exchangers in production. Thus, the application of flux with the dry method shows several advantages over the wet method, and the proposed LPCS technology is a new method.…”
Section: Preliminary Quality Evaluation Of the Sprayed Flux Layersmentioning
confidence: 99%
“…The use of the wet method increases the risk of contamination of the flux suspension with, for example, dust, metal particles and so on, and requires additional drying after the application process. Milani [33] showed that proper drying influences the mechanical properties of brazed joints and reduces the number of defective heat exchangers in production. Thus, the application of flux with the dry method shows several advantages over the wet method, and the proposed LPCS technology is a new method.…”
Section: Preliminary Quality Evaluation Of the Sprayed Flux Layersmentioning
confidence: 99%
“…Thermal response for the human body was studied by Zeiler et al [31] using fingertips as control sensor for personalized heating. Thermal effect of Nocolok flux was investigated on heat exchanger brazen joint by Milani et al [32]. Investigation of a 3D induced charge on a micro mixer having charged polarized particle was studied by Raad et al [33].…”
Section: Introductionmentioning
confidence: 99%